Ashes never lie [large type] - Goldberg, Lee, 1962- (Goldberg, Lee, 1962- Sharpe & Walker series, 2024)
"Vacant homes in a new housing development are erupting into flames in broad daylight with no apparent cause. It's a perplexing mystery for dogged arson investigator Walter Sharpe and his restless new partner, Andrew Walker, an ex US marshal who craves action. But as they puzzle over the blazes, another home miles away burns to the ground, leaving a man's corpse in the ashes and homicide detectives Eve Ronin and Duncan Pavone demanding answers. The burn patterns and charred body tell Sharpe a bizarre story that only creates more questions for Eve. So the four detectives team up to find the answers. Their investigation into the two unrelated cases leads to one shocking discovery after another. Now they must gamble their lives to unmask a brilliant arsonist, crack open a massive swindle, track down a desperate fugitive with a terrifying secret, and race against time to save thousands of people from an agonizing death."--